The agricultural landscape of Hellenistic Artaxata - Orendi , Andrea (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
Archaeobotanical research in Armenia is ongoing since many decades but analyses on Hellenistic archaeobotanical assemblages, however, are scarce. From 2018 to 2022 excavations of the Armenian-German Artaxata Project focused on the Lower City of the former capital of the Armenian Kingdom. Systematic sampling of the archaeological structures on Hill XIII resulted in hundreds of analysed macro remains. Although low in number, the charred seeds and fruits allow us to get an impression about the diet and the agricultural landscape of Hellenistic Artaxata. Attention will be paid both on the cultivated plants and the weed flora. According to the charred plant finds, the crop remains are clearly dominated by cereals with naked wheat as the most common cereal species found at Artaxata. The weed flora points to an open landscape with wet habitats in the vicinity of the excavation area. In sum, the agriculture of the Hellenistic kingdom was based on minimising the risk of crop failure by relying on the cultivation of a high range of crops which grow in different growing conditions and need different cultivation methods.